Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Menganyam Menggunakan Kertas Pada Anak Usia 5-6 Tahun di TK Raudatussibyan Al- Mannan Bagik Manis - Aini, Rokyal; Hadiyaturrido; Hadi, Mashal (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Improving Children's Fine Motoric Skills Through Weaving Activities Using Paper in Children Aged 5-6 Years at Raudatussibyan Al-Mannan Bagik Manis Kindergarten for the 2022/2023 Academic Year. This research was conducted at Raudatussibyan Al-Mannan Bagik Manis Kindergarten with a total number of children in group B1 at Raudatussibyan Al-Mannan Bagik Manis Kindergarten consisting of 16 children including 12 boys and 4 girls. This type of research is classroom action research (CAR) with 4 stages, namely planning, implementing, observing and reflecting. This research was conducted in 2 cycles, each cycle consisting of 8 meetings. Data collection techniques in this study used observation and tests of weaving activities. Based on the data from the classroom action research presented, it can be concluded that through weaving activities using paper can improve the fine motor skills of children in Kindergarten Raudatussibyan Al-Mannan Bagik Manis. This is indicated by an increase in the indicators of the results of children's fine motor skills as follows: Observation results of children's activities during learning by using weaving activities Observations of children's activities while participating in learning increased gradually. In cycle I, the results of children's activities while participating in the learning process through weaving activities using paper, namely 60% with the criteria for Starting to Develop (MB), and in cycle II increased to 80% with the criteria Developing According to Expectations (BSH). Thus the child's activity during the learning process increases through weaving activities using paper. While children's fine motor skills have increased, it can be seen from the results of the research and discussion that has been carried out, it can be concluded that learning through weaving activities using paper can improve children's fine motor skills at Raudatussibyan Al-Mannan Bagik Manis Kindergarten in the 2022/2023 Academic Year. This is shown by the increase in children's fine motor skills, namely from the initial condition that there were 6 children or 37.5% who had not yet developed, in cycle I there were 4 children or 25%, in cycle II none were undeveloped. In the initial conditions the number of children who started to develop was 8 people or 50%, in the first cycle there were 5 children or 31.25%, in the second cycle there were 2 children or 12.5% who started to develop, for children to develop as expected in the initial conditions as many as 2 children or 12.5%, in cycle I as many as 6 children or 37.5%, in cycle II as many as 9 children or 56.25%, while children developed very well in the initial conditions there were none, in cycle I as many as 1 child or 6.25% and in cycle II as many as 5 children or 31.25%.